Relación entre el funcionamiento familiar y desempeño lector de los estudiantes del grado quinto de una Institución Educativa de Riohacha. (2021)
The objective of this thesis was to determine the relationship between family functioning and reading performance of fifth grade students 1 of the Denzil Educational Institution School Headquarters Tawaira. For this, a Non-Experimental investigation was carried out, Transactional and Descriptive, with a Quantitative Research Method and its design of research is Descriptive Correlational.